Perancangan Baru Pusat Perawatan Pasca Melahirkan Di Tangerang Selatan Dengan Pendekatan Healing Environment - Shatry 'Ammaara, Tsabitah; Nur Hardiansyah, Mahendra; Sri Ismiranti, Athifa (eProceedings of Art & Design, 2024)
In Indonesia, child-rearing responsibilities predominantly fall on women due to patriarchal cultural influences that assign household and caregiving duties solely to mothers. This imbalance increases the risk of mental health issues for women, including postpartum depression, which is often caused by hormonal changes and the heavy burden of caregiving. The postpartum period is crucial for the recovery of both mother and baby, yet postpartum care facilities in Indonesia remain limited and insufficient in providing comfort and privacy. A survey of mothers who gave birth in the past two years reveals that many feel inadequately supported in their physical and mental recovery. This study employed a survey methodology to assess the needs of postpartum women and examined the potential of postpartum care centers adopting a healing environment concept. Findings indicate that implementing the healing environment concept in the interior design of postpartum care centers can create a calming atmosphere, expedite recovery, and raise awareness of the importance of postpartum care and the division of child-rearing responsibilities. This research highlights the need for more comprehensive postpartum care facilities in Indonesia and provides insights into how design can enhance maternal health outcomes. Keywords: Interior, Mental, Recovery, Healing, Postpartum.